Investigation of the perception characteristics of multiple impact sounds occurring from the manipulation of electronic devices - Jeong, Seongyoung; Park, Buhm; Kwak, Yunsang; Park, Junhong (Journal of mechanical science and technology, 2019)
Electronic devices must be quiet during manipulation for operations. In addition, the sounds need to show distinct impression to satisfy the user’s auditory experience and indicate the completion of an operation. The sounds occur in a short time from frictional contact and the consequent structural vibration when a user operates a device. In this study, the impact sound during printer cassette insertion is analyzed. The rail vibration during closure movement generates continuous sound. This movement ends with the impact sound from contact between the cassette and printer body. The sounds occur as clicking sounds with double impacts separated by a short interval. This clicking sound is important serving as an indicator of completed insertion. The user’s perception of this complex sound is investigated. A physical index to quantify the generated sound is proposed to assist comparisons between printers. Prony’s method was used to characterize the sound features including duration, double impact interval, magnitudes, and decay rates. From the extracted features, artificial clicking sounds were simulated for sound quality evaluations. Auditory experiments were performed to investigate the user’s preference for the separated rail and impact noises. The just noticeable difference was defined to classify the important factors influencing the perception characteristics.